Evaluation of Waiting Time for Drug Services at the Umban Sari Rumbai Health Center Pharmacy Installation - Sari, Seftika; Halim, Putri Muhmida; Habib, Qory Nabilah; Oriendhini, Salsa; Rahmayani, rRhmayani; Dwi, Rahmah Safrita (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Ibuprofen According to the Indonesian Ministry of Health, the waiting time for non-compounded drug services is 30 minutes, while the waiting time for compounded drug services is 60 minutes. This study is a descriptive observational study to evaluate the Waiting Time for Drug Services at the Umban Sari Rumbai Health Center Pharmacy Installation. The study period was April, with 110 samples. The study was conducted by calculating the waiting time for compounded and non-compounded drug prescription services, then a descriptive analysis was carried out and compared with the minimum service standards for waiting time for both compounded and non-compounded drugs. The waiting time data was converted into minutes and then the mean value was calculated using statistics. In the study of the analysis of the waiting time for prescription services at the Umban Sari Rumbai Health Center, Pekanbaru, there were 2 types of waiting time for prescription services studied, namely the type of drug consisting of compounded and non-compounded prescriptions. The number of samples obtained was 110 prescriptions, consisting of 102 non-compounded prescriptions and 8 compounded prescriptions with percentages of 92.73% and 7.27% respectively. The average waiting time for prescription services at the Umban Sari Rumbai Health Center pharmacy installation was 3.97 minutes for non-compound prescriptions and 11.37 minutes for compound prescriptions. These results are in accordance with the Decree of the Minister of Health of the Republic of Indonesia Number 129 of 2008 that the waiting time for prescription services for non-compound drugs is 30 minutes and compound drugs 60 minutes. Based on the results of the study, it can be concluded that the average time needed to complete a compound prescription is 11.37 minutes and to complete a non-compound prescription is 3.97 minutes. This shows that the waiting time for prescription services at the Umban Sari Rumbai Health Center pharmacy installation has met the minimum service standards, namely 30 minutes for non-compound prescriptions and 60 minutes for compound prescriptions.